COVID-19 and the judiciary: the case for access to testing Sudhi versus Union of India - Uberoi, Diya (International Journal Of Community Medicine And Public Health, 2020)
In an effort to protect citizens’ right-to-health, the Supreme Court of India on April 8th ordered the government to make COVID-19 testing free in all private hospitals and labs. The Court’s decision in Sudhi v. Union of India marked a significant step towards ensuring that all people, especially poor workers in the informal sector have access to necessary care. Five days later, however, after facing objections from private companies and the state, the Supreme Court reversed its previous order and made testing free for only those living below the poverty line, an obligation already mandated under the National Health Policy Scheme.This commentary suggests that judicial action should be strengthened, not hampered, in times of global health crisis. While no state has unlimited resources to ensure the protection of health, the judiciary should be emboldened to hold the state to account.